2018
DOI: 10.1148/radiol.2017170281
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma and Dual-Energy CT: Diagnostic Accuracy of Virtual Noncalcium Technique for Detection of Bone Marrow Infiltration of the Spine and Pelvis

Abstract: Purpose To determine the diagnostic performance of dual-energy computed tomography (CT) for detection of bone marrow (BM) infiltration in patients with multiple myeloma by using a virtual noncalcium (VNCa) technique. Materials and Methods In this prospective study, 34 consecutive patients with multiple myeloma or monoclonal gammopathy of unknown significance sequentially underwent dual-energy CT and magnetic resonance (MR) imaging of the axial skeleton. Two independent readers visually evaluated standard CT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(92 citation statements)
references
References 35 publications
0
86
0
6
Order By: Relevance
“…Computed tomography is particularly useful for further characterization of tumors with mineralized matrix and of sclerotic tumors. Most recently the application of dual energy CT virtual non-calcium algorithms has proven to be a valuable tool in the assessment of MBD lesions and disease load [33][34][35] as well as in identifying focal biopsy targets [36]. Moreover, CT is also useful for further characterization of tumors in the cortex, paracortical, and periosteal locations.…”
Section: Cross-sectional Imaging: Mri and Ctmentioning
confidence: 99%
“…Computed tomography is particularly useful for further characterization of tumors with mineralized matrix and of sclerotic tumors. Most recently the application of dual energy CT virtual non-calcium algorithms has proven to be a valuable tool in the assessment of MBD lesions and disease load [33][34][35] as well as in identifying focal biopsy targets [36]. Moreover, CT is also useful for further characterization of tumors in the cortex, paracortical, and periosteal locations.…”
Section: Cross-sectional Imaging: Mri and Ctmentioning
confidence: 99%
“…7). Mit deren Hilfe konnte gezeigt werden, dass auch ein nicht osteolytischer Knochenmarkbefall im Achsenskelett CT-grafisch detektierbar ist [53,54]. Die Technik kann außerdem dazu verwendet werden, gezielt fokale Knochenläsionen zu biopsieren, die im her- kömmlichem CT okkult sind [55].…”
Section: Zukünftige Entwicklungenunclassified
“…The use of a three-material decomposition model allows for the creation of VNCa images by subtracting calcium from CT data. To date, few studies have reported on the use of this technique to directly depict (a) trauma-associated bone marrow edema in the extremities (9,10) or spine (11)(12)(13)(14)22,23) or (b) malignant bone marrow infiltration (15,16,24). However, to our knowledge, this is the first and largest prospective study to address the bone marrow edema associated with inflammatory rheumatic disorders when using dual-energy CT (25,26).…”
Section: Quantitative Analysis Of Bone Marrow Ct Numbersmentioning
confidence: 99%
“…However, the inability of conventional single-energy CT to depict bone marrow edema, which is regarded as the early stage of active inflammation, significantly limits its clinical utility (15,27). More recently, it has also been documented that dual-energy CT with the addition of color-coded VNCa images to standard CT images could significantly improve visual sensitivity of readers in the detection of bone marrow lesions, from 69.6% to 91.3% (16). Results from our study support the hypothesis that dual-energy CT with reconstruction of VNCa images has enabled both qualitative (visual) and quantitative analysis of bone marrow edema of sacroiliac joints in study participants with axSpA, with a precision comparable to that of MRI.…”
Section: Disclosures Of Conflicts Ofmentioning
confidence: 99%